Implementation of Supply Chain Management Using ERP Odoo (Case Study of PT Mas Arya Indonesia) - Bayu Setyo Nugroho; Mafaza Ayudia Putri; Mohammad , Mohammad; Muhamad Arjunajah Dzalfajri; Ryan Rizkiyanto; Siti Wahyuni Setianingrum (Cita konsultindo, 2023)
The rapid development of technology, companies are expected to be able to make good use of technology so that business activities can run effectively and efficiently. Handling the production process which was originally carried out manually is slowly being replaced by machines that help manage data in a computerized manner. The use of the system helps companies in terms of human resources, finance, and product management. One of the activities that cannot be separated from production activities is inventory management. Entrepreneurs can use a variety of applications to help manage inventory. The ERP application with the Odoo system is one of the applications available for companies, from managing suppliers of raw material suppliers to calculating the total costs to be paid automatically. The case study in this research is the use of the Odoo application to assist the production process and count stock inventory of PT Mas Arya Indonesia, which operates in the garments sector.